Pengaruh Good Corporate Governance (GCG), Profitabilitas, Struktur Modal dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Sektor Keuangan Sub Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2019-2023 - Suryadi, Anggi; Lasmana, Andy; Melani, Maria Magdalena (Innovative: Journal Of Social Science Research, 2025)
This study seeks to evaluate the influence of Good Corporate Governance (GCG), profitability, capital structure, and business size on the valuation of financial sector firms, particularly in the banking sub-sector, listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The population consists of all banking firms listed on the Indonesia Stock Exchange (IDX), totalling 47 organisations over the 2019-2023 research period. The research sample consisted of 22 financial sector companies from the banking sub-sectors, chosen by purposive sampling according to specific criteria. The utilised methodology employs Eviews software. This study's findings indicate that Good Corporate Governance (GCG) has a partial positive influence but does not significantly impact company value; profitability positively influences and significantly affects company value; capital structure negatively influences but does not significantly affect company value; and company size negatively influences without a significant effect on company value. Simultaneously, Good Corporate Governance (GCG), profitability, capital structure, and company size have a positive and significant effect on the valuation of financial sector firms in the banking sub-sector listed on the Indonesia Stock Exchange from 2019 to 2023.